Desperately Seeking Dissonance: Identifying the Disconfirming Case in Qualitative Evidence Synthesis. (January 2013) - Booth, Andrew; Carroll, Christopher; Ilott, Irene; Low, Lee Lan; Cooper, Katy
Actively seeking the disconfirming or deviant case is properly regarded as a hallmark of trustworthiness in primary qualitative research. The need to subject emergent theory to such testing is no less important within qualitative systematic reviews. There is, as yet, little available guidance on how to implement such strategies. Few researchers have described the practicalities of seeking the disconfirming case. We survey the methodological literature to gain a better understanding of how systematic reviews of qualitative research handle the disconfirming case. We reflect on our own experience from three recent qualitative evidence syntheses. We describe how reviewers might actively manufacture opportunities to identify discrepant or refutational findings. We conclude by outlining possible methods by which a team might integrate active seeking of a disconfirming case within the overall review process.